Recirculator SALO design - work executed in 2006 - Guk, I.S. (Вопросы атомной науки и техники, 2007)
In 2006 development of the recirculator design was carried out within the limits of three programs. With the purpose to decrease of a beam traversal emittance and energy straggling the new system of injection allowing smoothly to control energy of a beam is offered and optimized. The magnetooptical recirculator system structure was optimized also. The basic aspects of recirculator operation in structure of the driver of subcritical assembly are in detail viewed. Alternatives embodying of beam transportation channels on a target are offered. Draft designs of all recirculator magnetic devices and the draft design of magnetic system as a whole are developed. В 2006 році розробка проекту рециркулятора виконувалась в рамках трьох програм. З метою зменшення поперечного эмітансу пучка та енергетичного разкиду запропонована і оптимізована нова система інжекції, яка дозволяє плавно змінювати енергію пучка. Оптимізована нова ізохронна структура магнітооптичної системи рециркулятора. Детально розглянуті основні аспекти роботи рециркулятора в складі драйвера підкритичної збірки. Запропоновані варіанти реалізації каналів транспортування пучка на мішень. Розроблені ескізні проекти всіх магнітних елементів рециркулятора та ескізний проект магнітної системи в цілому. В 2006 году разработка проекта рециркулятора осуществлялась в рамках трёх программ. С целью уменьшения поперечного эмиттанса пучка и энергетического разброса предложена и оптимизирована новая система инжекции, позволяющая плавно регулировать энергию пучка. Оптимизирована новая изохронная структура магнитооптической системы рециркулятора. Подробно рассмотрены основные аспекты работы рециркулятора в составе драйвера подкритической сборки. Предложены варианты реализации каналов транспортировки пучка на мишень. Разработаны эскизные проекты всех магнитных элементов рециркулятора и эскизный проект магнитной системы в целом.